Style Analysis: Asset Allocation & Performance Evaluation of Indonesian Equity Funds, April 2004 – March 2009 - Mangiring, Boniarga; Husodo, Zäafri Ananto (The Indonesian Capital Market Review, 2010)
This paper explores investment styles and risk exposures of mutual funds in Indonesia using Sharpe's return-based style analysis, a quadratic optimization of an asset class factor model, proposed by William F. Sharpe in 1992. The research observes nine sectoral asset class indexes and ifteen survivor Indonesian equity funds within April 2004 - March 2009. The results suggest that the infrastructure sector has the biggest exposure on average. This study also measures the relative performance of the funds with respect to their style benchmarks. The results indicate that the nine funds have been able to beat their style benchmarks on average. From all funds, Fortis Ekuitas is the best fund based on its average monthly selection return.